KEALPAAN PERUSAHAAN TIDAK MENDAFTARKAN PEKERJA BERKAITAN JAMINAN KESEHATAN DAN KESELAMATAN KERJA HINGGA HILANGNYA NYAWA PEKERJA - Hendra Sulisthio (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT             The Social Guarantee of Labor as on kind of social guarantee which gives both protection and welfare for labor human is participates in development activities by reducing unconvinced future, creating work serenity and tranquility efforts ; therefore, it can improve both production and productivity. The benefits in performing the social guarantee are very enjoyed by the labor, especially for low income workers even minimum levelof income,in which it do not cut their wagws for treatment costs if they or their family member are sick.               This research is analytic-deskriptive feature, it is the research aimed to obtain entire, complete and systematic description about the responsibility of the Limited Company (PT) in registering their workers as the Social Guarantee Participant of Labor in Samarinda City. It is analytic fuature, because both symptoms abd facts stated by respondent, then, will analyzed for various law aspects either from limited company regulation or civil law and labor law. The implemented approach is juridical-empirical, that is a research which analyzes the regulations of law then related with data and behavioral of the doers concerned with the title of research.                The responsibility of Limited Company in registering their workers as the Social Guarantee Participant of Labor is accordance with mandate of Act Number 13 Year 2003 about Labor, Act Number 3 Year 1992 about the Social Guarantee of Labor, that authorizes all entrepreneurs exactly to pay the wages of their workers above Rp. 1.000.000,- (one million rupiah) or employing 10 workers, it is a must to register them for social guarantee of labor. Some factors caused Limited Companies do not register their workers as the Social Guarantee of Labor are many of them are in contract system and there is Unregistered Company (PWBD), low-income workers, and under regional wages, also there are many companies state that the Social Guarantee of Labor Program is not their responsibility. In solving the case of the Limited Companies which do not register their workers as the guarantee social participant is by performing the socialization to all companies and also creating a collaborative with Justice Party to take action againts the companies that do not register their workers as the Social Guarantee Participant formally.  Keywords : The Responsibility of Company, The Social Guarantee Participant of Labor.